An experimental study of the effects of SNPs in the TATA boxes of the GRIN1, ASCL3 and NOS1 genes on interactions with the TATA-binding protein - E. B. Sharypova; I. A. Drachkova; I. V. Chadaeva; M. P. Ponomarenko; L. K. Savinkova (Вавиловский журнал генетики и селекции)
The GRIN1, ASCL3, and NOS1 genes are associated with various phenotypes of neuropsychiatric disorders. For instance, these genes contribute to the development of schizophrenia, Alzheimer’s and Parkinson’s diseases, and epilepsy. These genes are also associated with various cancers. For example, ASCL3 is overexpressed in breast cancer, and NOS1, in ovarian cancer cell lines. Based on our findings and literature data, we had previously obtained results suggesting that the single-nucleotide polymorphisms (SNPs) that disrupt erythropoiesis are highly likely to be associated with cognitive and neuropsychiatric disorders in humans. In the present work, using SNP_TATA_Z-tester, we investigated the influence of unannotated SNPs in the TATA boxes of the promoters of the GRIN1, ASCL3, and NOS1 genes (which are involved in neuropsychiatric disorders and cancers) on the interaction of the TATA boxes with the TATA-binding protein (TBP). Double-stranded oligodeoxyribonucleotides identical to the TATA-containing promoter regions of the GRIN1, ASCL3, and NOS1 genes (reference and minor alleles) and recombinant human TBP were employed to study in vitro (by an electrophoretic mobility shift assay) kinetic characteristics of the formation of TBP–TATA complexes and their affinity. It was found, for example, that allele A of rs1402667001 in the GRIN1 promoter increases TBP–TATA affinity 1.4-fold, whereas allele C in the TATA box of the ASCL3 promoter decreases the affinity 1.4-fold. The lifetime of the complexes in both cases decreased by ~20 % due to changes in the rates of association and dissociation of the complexes (ka and kd, respectively). Our experimental results are consistent with the literature showing GRIN1 underexpression in schizophrenic disorders as well as an increased risk of cervical, bladder, and kidney cancers and lymphoma during ASCL3 underexpression. The effect of allele A of the –27G>A SNP (rs1195040887) in the NOS1 promoter is suggestive of an increased risk of ischemic damage to the brain in carriers. A comparison of experimental TBP–TATA affinity values (KD) of wild-type and minor alleles with predicted ones showed that the data correlate well (linear correlation coefficient r = 0.94, p < 0.01).